2011
DOI: 10.3109/13880209.2011.591806
|View full text |Cite
|
Sign up to set email alerts
|

Novel flavonoids with antioxidant activity from a Chenopodiaceous plant

Abstract: Two new flavonoids, quercetin-6,4'-dimethoxy-3-fructo-rhamnoside 1 and quercetin-4'-methoxy-3-fructo-rhamnoside 2 in addition to five known compounds (kaempferol-4'-methoxy-3-rutinoside 3, kaempferol-7-O-rhamnoside 4, kaempferol-3,7-O,O-dirhamnoside 5, quercetin 6, and kaempferol 7) were isolated. Oral administration of total ethanol, diethyl ether, chloroform, ethyl acetate and n-butanol extracts showed no signs of toxicity up to (5 g/kg. b.wt.). All extracts and isolated compounds showed varied antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…Data in table (1) revealed that methanolic extract and PAPs contained average total polyphenols values of 89.7 and11.16 mgGAE/g dry weight, respectively. PAPs yielded lower total phenols content than MeOH extract.…”
Section: Results and Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Data in table (1) revealed that methanolic extract and PAPs contained average total polyphenols values of 89.7 and11.16 mgGAE/g dry weight, respectively. PAPs yielded lower total phenols content than MeOH extract.…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…It was found as 74.7 and 3.18 mg QE/g for MeOH extract and PAPs, respectively ( Table 1). The number of hydroxyl groups and substitution with electron-donating alkyl or methoxy groups of flavonoids cause an increase in their antioxidant activity (Awaad et al, 2012 HPLC separation of flavonoids and phenolic compounds:-High-performance liquid chromatograph equipped with a diode array detector was used to determine the flavonoids and phenolic compounds in the methanol extract of Plumeria alba leaves. Table 2 shows the amount of nine phenolic compounds, including, pyrogallol, rosmaric, ferrulic acid, vanillic acid, p.coumaric acid, ellaglic acid, salycillic acid, cinamic acid and protocatechuic and ten flavonoids, including catechin, Epicatechin, rutin, hisperedin, narenigin, quercetin, hesperetin, apigenin, kaempferol and Diosmitin in 100 g dry matter of MeOH extract of Plumeria alba leaves.…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…Nevertheless, literature review connects the bioactivity to many compounds. Flavonoids have been associated to various biological activities amongst which antiviral and antioxidant effects [53]. Kulisic-Bilusic et al [54] reported antioxidant activities for procyanidins and anthocyanins.…”
Section: Effect Of the Extraction Parameters On Thementioning
confidence: 99%
“…The results indicated that the hepatoprotection by the flavonoid-enriched fraction was due to its antioxidant properties through enhancing the activity of SOD, GPx, and CAT ( Figure 4). As a type of phenolic compound, flavonoids have attracted increasing attention particularly for their attractive antioxidant activities (Awaad et al, 2012;Prommuak et al, 2008). DOI: 10.3109/13880209.2015.1010737 They have also been reported to offer a promising source of potential antioxidants (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%